2021
DOI: 10.3390/separations8100174
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Sea Urchin Roe (Strongylocentrotidae)—Study of Composition and Storage Conditions

Abstract: Although the roe of sea urchins inhabiting the Far Eastern seas possesses many healing properties and may be used as a dietary product, a reduction and deterioration in its nutritional quality during storage occurs. Therefore, in order to make sea urchin products widely accessible to the world population, it is very important to have appropriate technology to keep the roe from spoiling. To store sea urchin roe for a long time, methods of pre-processing sea urchin gonads before freezing were tested. In terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The protein levels in this study were lower when compared to the protein levels of D. setosum from Terengganu Malaysia, ranging from 36.21 -50.14% (Rahman et al, 2023). Meanwhile, the protein content of this study is almost the same as the research of Matveeva et al (2021); the protein content of S. intermedius gonads is 13.9%, and S. nudus is 13.8%. Research by Archana&Babu (2016) found the protein content of S. variolaris gonads to be 12.10% and P. lividus 12.03%.…”
Section: Protein Contentcontrasting
confidence: 48%
See 2 more Smart Citations
“…The protein levels in this study were lower when compared to the protein levels of D. setosum from Terengganu Malaysia, ranging from 36.21 -50.14% (Rahman et al, 2023). Meanwhile, the protein content of this study is almost the same as the research of Matveeva et al (2021); the protein content of S. intermedius gonads is 13.9%, and S. nudus is 13.8%. Research by Archana&Babu (2016) found the protein content of S. variolaris gonads to be 12.10% and P. lividus 12.03%.…”
Section: Protein Contentcontrasting
confidence: 48%
“…The results of D. setosum gonad fat content differ from those of Rahman et al (2023), between 20.17% -26.18%. The fat content of S. intermedius gonads is 7.3%, and S. nudus is 6.3% (Matveeva et al, 2021). The protein content of S. variolaris gonads was 4.98% and P. lividus 3.05% (Archana & Babu, 2016).…”
Section: Fat Contentmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Matveeva et al [22] corroborated that urchin gonads are characterized by their high content of essential amino acids such as mainly glutamine, asparagine, glycine, alanine, and arginine, which are responsible for the flavor properties of these products. Moreover, sea urchin roe present high levels of enzymatic activity such as protein proteolysis, lipid hydrolysis, oxidation glycogen, phosphocreatine, ATP, and the formation of melanoidin pigments [23] that substantially enhance the quality of the fish sauces in a short time [22]. Considering both of the aspects above mentioned, i.e., its nutritional characteristics and its enzymatic activity, sea urchin is an ingredient with the potential to improve the nutritional and sensory characteristics of fish sauces and to act as a fermentation activator.…”
Section: Introductionmentioning
confidence: 99%
“…Sea urchin caviar is a rich source of various biologically active substances and is of particular value in the diet of the population [1,2]. It contains full proteins and sulfated polysaccharides [3], a large set of fat-soluble and water-soluble vitamins, macronutrients, and trace elements [4] of pigments, carotenoids [5], and naphthoquinones [6].…”
Section: Introductionmentioning
confidence: 99%